EFEKTIVITAS MODEL DISCOVERY LEARNING DITINJAU DARI PEMAHAMAN KONSEP MATEMTIS SISWA KELAS XI IPS SMA NEGERI 1 GAMPING - Khamidah Khamidah; Kristina Warniasih (Delta: Jurnal Ilmiah Pendidikan Matematika, 2019)
One of the goals of mathematics learning is that students are expected to have good understanding mathematics concept abilities. The application of discovery learning model in the process of learning mathematics is one of the learning modelsthat can improve students understanding of mathematics concepts. The learning process uses the discovey learning model so that students can find the concepts of the material being studied and can conclude their own concepts that have been found based on their ability to understand. This research aims to determine that: (1) students understand the mathematics concepts of discovery learning model in effective;(2) students understand the mathematics concepts of conventional learning model in effevtive; (3) the effectiveness of discovery learning model and conventional learning for understanding mathematics concepts, and to know in 11th Senior High School at SMA N 1 Gamping. This type of research is an experimental quasi experiment with research design Posttest Only Control Design. The population in this study were students of class XI IPS SMA N 1 Gamping. The sample in this study was class XI IPS 1 as an experimental class and class XI IPS 2 as a control class. The instrument used in the study was the observation sheet of the implementation of learning and the students understanding mathematics concepts test questions. Analysis of the data used is the t-test and the prerequisite test used are normality and homogeneity test. The result showed that using discovery learning model and conventional learning model were effective that students understand the mathematics concepts, and learning using discovery learning model was more effective than conventional learning model when viewed from students understand the mathematics concepts.